2010
DOI: 10.1186/1471-2156-11-65
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism, linkage disequilibrium and geographic structure in the malaria parasite Plasmodium vivax: prospects for genome-wide association studies

Abstract: BackgroundThe ideal malaria parasite populations for initial mapping of genomic regions contributing to phenotypes such as drug resistance and virulence, through genome-wide association studies, are those with high genetic diversity, allowing for numerous informative markers, and rare meiotic recombination, allowing for strong linkage disequilibrium (LD) between markers and phenotype-determining loci. However, levels of genetic diversity and LD in field populations of the major human malaria parasite P. vivax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 56 publications
4
51
1
7
Order By: Relevance
“…Sixty-five (7.4%) of the 883 P. vivax isolates analyzed worldwide had the FF haplotype, but they originated from only three countries: Brazil (Paragominas and Granada), 14,26 Honduras, 24 and Papua New Guinea. 9 More extensive genotyping at and surrounding the pvmdr-1 locus might indicate whether these haplotypes share a common ancestor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixty-five (7.4%) of the 883 P. vivax isolates analyzed worldwide had the FF haplotype, but they originated from only three countries: Brazil (Paragominas and Granada), 14,26 Honduras, 24 and Papua New Guinea. 9 More extensive genotyping at and surrounding the pvmdr-1 locus might indicate whether these haplotypes share a common ancestor.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed newly obtained SNP data for 13 isolates collected in Acrelâ ndia, 21 in Plácido de Castro and 46 in Remansinho, and data previously obtained with the same typing strategy, for 37 isolates from Plá cido de Castro and 111 from Granada. 14 Of five SNPs assayed, two were monomorphic in the Western Amazon Basin of Brazil: all 228 isolates examined had the amino acid replacements (relative to the pvmdr-1 sequence of Sal-1 strain, which is defined as wild type) N89S and M908L (Table 1). Although these changes are not putatively associated with CQ resistance, they can be useful in tracing the geographic origin of pvmdr-1 haplotypes carrying mutations Y976F and F1076L, which in turn might underlie CQ resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…WGA, a method that has been used in similar molecular epidemiological studies, [25][26][27][28] was performed prior to genotyping to increase the amount of P. vivax DNA for analysis. The multiple displacement amplification (MDA) method used in this study has been shown to result in a higher yield of non-artifact DNA template and reduced amplification bias compared with PCR-based WGA methods.…”
Section: Resultsmentioning
confidence: 99%